Comparative analysis of PFASs concentrations in fur, muscle, and liver of wild roe deer as biomonitoring matrices - Draghi, Susanna; Curone, Giulio; Risoluti, Roberta; Materazzi, Stefano; Gullifa, Giuseppina; Amoresano, Angela; Spinelli, Michele; Fontanarosa, Carolina; Pavlovic, Radmila; Pellegrini, Alberto; Fidani, Marco; Cagnardi, Petra; et al. (Frontiers in Veterinary Science, 2024)
BackgroundRecently, environmental pollution has become a significant concern for human, animal, and environmental health, fitting within the “One Health” framework. Among the various environmental contaminants, per- and polyfluoroalkyl substances (PFASs) have gathered substantial attention due to their persistence, bioaccumulation, and adverse health effects. This study aimed to compare the levels of 12 PFASs in the fur, liver, and muscle of wild roe deer to evaluate the feasibility of using fur as a non-invasive biomonitoring matrix.MethodsA total of 20 male and 20 female roe deer aged between 12 and 24 months were randomly sampled from a hunting area in Northern Italy. Samples of fur, muscle, and liver were collected post-mortem, and PFAS concentrations were measured using a validated UHPLC-HRMS method.Results and discussionThe results indicated significant differences in PFAS concentrations among the three matrices. Fur, although easier to sample and store, showed highly variable PFAS levels, with different detection frequencies compared to the muscle and liver. PFASs such as PFHxA were more frequently detected in fur than in the liver and muscle, while compounds such as PFBA, PFPeA, PFHpA, PFDA, PFHxS, 6-2 FTS, and 8-2 FTS were less frequently detected in fur. In conclusion, while fur presents many practical advantages for biomonitoring, such as non-invasive sampling and stability, its use is complicated by varying detection frequencies and concentration levels. These aspects, together with the use of a single sampling technique, can be considered a limitation of the study. Notably, compounds such as PFOA, PFNA, and PFOS showed partially similar detection frequencies across the matrices, suggesting potential interest for further research. This study offers new perspectives on the use of fur for environmental monitoring, highlighting the need for more extensive research to understand the relationship between PFAS concentrations in fur and other biological matrices. Future studies should focus on methodological improvements in extraction and quantification techniques for PFASs in fur to enhance their reliability as a biomonitoring tool.